2021
DOI: 10.3390/ma14185183
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Fracture Properties of Long Fiber Reinforced Geopolymer Composites

Abstract: The aim of the article is to analyze the structure and mechanical properties in terms of the cracking mechanics of geopolymer composites based on fly ash and river sand, as well as metakaolin and river sand with three types of reinforcement material: glass fiber, carbon fiber, and aramid fiber, in terms of their use in additive manufacturing. Geopolymer composites were reinforced with fibers in a volume ratio of 0.5%, 1.0%, and 2.0%. Subsequently, these samples were subjected to bending strength tests in accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 70 publications
2
23
0
Order By: Relevance
“…The addition of calcium compounds such as calcium oxide, calcium hydroxide, and calcium rich by-product such as ground granulated blast furnace slag can also reduce the setting time of geopolymers [ 12 , 17 , 18 , 19 , 20 , 21 , 22 ]. The alkali activated materials using calcium rich by-products form two-dimensional structure [ 23 , 24 ]. It may affect the properties of geopolymer such as long-term properties and resistance to the chemical agents, but its effect on the geopolymer structure is unclear [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of calcium compounds such as calcium oxide, calcium hydroxide, and calcium rich by-product such as ground granulated blast furnace slag can also reduce the setting time of geopolymers [ 12 , 17 , 18 , 19 , 20 , 21 , 22 ]. The alkali activated materials using calcium rich by-products form two-dimensional structure [ 23 , 24 ]. It may affect the properties of geopolymer such as long-term properties and resistance to the chemical agents, but its effect on the geopolymer structure is unclear [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The alkali activated materials using calcium rich by-products form two-dimensional structure [ 23 , 24 ]. It may affect the properties of geopolymer such as long-term properties and resistance to the chemical agents, but its effect on the geopolymer structure is unclear [ 23 , 24 ]. Considering the disadvantages of heat curing and the use of high calcium source materials, the addition of calcium compound is more beneficial since the appropriate amount of calcium compound is effective for fast setting as well as the enhancement of compressive strength [ 17 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…(2) the formulation of aggregates [75][76][77][78]80]; and (3) specific modifications, including reinforcing additives [59,121], agents controlling the geopolymer macrostructure [58,59], and curing conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the reference samples were prepared based on metakaolin and fly ash without the addition of fibers. The percentage selection of fibers was based on the previous research, including the best results [32]. The previous results showed that the highest mechanical properties values were obtained in the 2% addition of aramid fibers to the metakaolin matrix.…”
Section: Sample Preparationmentioning
confidence: 99%
“…The previous results showed that the highest mechanical properties values were obtained in the 2% addition of aramid fibers to the metakaolin matrix. The other samples for comparison were based on different fibers as well as different matrices and different percentages of fibers [32]. In the next step, the prepared pastes were placed on a vibrating table (Cracow University of Technology, Cracow, Poland) in molds to remove air bubbles.…”
Section: Sample Preparationmentioning
confidence: 99%